Isu Isu Kontemporer dalam Pendidikan Islam di Madrasah Ibtidaiyah - Nabila Joti Larasati; Zulhijrah; Sedya Sentosa (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2024)
This study aims to determine the Contemporary Issues in Islamic Education in Madrasah Ibtidaiyah. The research method used in this research is library research. Data collection techniques by exploring data through literature review, reading, reviewing, and recording data from various sources of relevant articles, journals and books. The results of the research show that contemporary Islamic education is an activity that is carried out in a planned and systematic manner to develop the potential of students based on the rules of Islamic religion at the present time. And with the development of the times and the advancement of technology, there are changes that occur, one of which is curriculum changes in learning.